Are restrictions of competition by sports associations horizontal or vertical in nature? - Oliver Budzinski; Stefan Szymanski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2014)
In this paper, we discuss from an economic perspective two alternative views of restrictions of competition by sports associations. The horizontal approach views such restrictions as an agreement among the participants of a sports league with the sports association merely representing an organization executing the horizontal cooperation. In contrast, the vertical approach views the sports association as being a dominant upstream firm enjoying a monopoly position on the market stage for competition organizing services, an important input for the actual product - the sports game. Taking the recent financial fair play (FFP) initiative by UEFA (the Union of European Football Associations) as an example, we demonstrate that the different views lead to different assessments of restrictive effects and, thus, matter for competition policy decisions. The economic story of the potential restrictive effect of FFP on players' and player agents' income may fit more plausibly to the horizontal approach, whereas the potentially anticompetitive foreclosure and deterrence effects of FFP may be economically more soundly reasoned by taking the vertical view.
Keywords: K21; L41; L42; L44; L83; 330; European competition policy; sports economics; financial fair play; horizontal agreements; vertical restrictions; European football; antitrust